Learning Language Naturally: Challenges and Opportunities - Wishnoebroto, Wishnoebroto (Humaniora, 2012)
Experts believed that the best way in learning language is through natural process, which means that learning should go through process of understanding concept. Grammar and all language features are mastered through practice in certain context. This article tries to find a model of information technology that may be suitable for learning English but without leaving the main functions of textbook as the center for knowledge and information through an approach called the Dynamic Immersion Approach. This approach tries to mimic the process of children in learning language. From the analysis it shows that despite many advantages from the new approach this program cannot produce natural language since it lacks the capability of producing informal language.